Flow characteristics of ternary blended self-consolidating cement mortars incorporating palm oil fuel ash and pulverised burnt clay - Hassan, I.; Ismail, Mohamed; Forouzani, P.; Majid, Z.; Mirza, J. (Elsevier BV, 2014)
This article aims at investigating the flow characteristics of self-consolidating cement mortars incorporating palm oil fuel ash (POFA) and pulverised burnt clay (PBC). These mortars were tested with respect to their flow spread. Fifteen (15) different cement mortar mixtures were prepared containing Ordinary Portland Cement (OPC) and a blend of POFA and PBC at 0%/0%, 5%/5%, 10%/5%, 10%/10% and 15%/15% as a replacement of OPC. Water-to-binder ratio (W/B) of 0.3, 0.35 and 0.4 were used in all the mortar mixtures. The flow spreads of the mortars were determined using a standard flow mould and subsequently the relative flow areas were measured. The effects of different W/B, high range water reducer (HRWR) dosage and the blend percentage of POFA and PBC on flow characteristics of the various mortars were analysed and reported. Results showed that the flow of the mortar increased with the increase in POFA/PBC content and HRWR dosage while it decreased at higher W/B. Nonetheless, higher dosage of HRWR resulted in the bleeding of mortar. This study also showed that blended POFA/PBC can be used up to 30% replacement with a maximum HRWR content of 2.5% to design and produce self-consolidating cement mortar and concrete.